2007
DOI: 10.1016/j.jvs.2007.02.072
|View full text |Cite
|
Sign up to set email alerts
|

Carotid intraplaque hemorrhage detected by magnetic resonance imaging predicts embolization during carotid endarterectomy

Abstract: Intraplaque hemorrhage as detected by carotid MRI predicts particulate embolization during the dissection phase of CEA. This imaging technique can be used to identify patients with increased intraoperative thromboembolic risk, and this could influence preventive strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
60
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 32 publications
3
60
1
Order By: Relevance
“…The high association of hemorrhage or fibrous tissue corresponded with previous findings. 9,12 In contrast, no reports have described the reduced association for lipid/necrosis. Signal intensity for each component in the carotid plaque is, in descending order, hemorrhage, lipid/necrosis, and fibrous tissue in any MR plaque imaging.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The high association of hemorrhage or fibrous tissue corresponded with previous findings. 9,12 In contrast, no reports have described the reduced association for lipid/necrosis. Signal intensity for each component in the carotid plaque is, in descending order, hemorrhage, lipid/necrosis, and fibrous tissue in any MR plaque imaging.…”
Section: Discussionmentioning
confidence: 97%
“…[5][6][7][9][10][11] Several investigators have compared MES during the exposure procedure for the carotid arteries in CEA with histopathologic findings of excised carotid plaque and have demonstrated that development of the MES was strongly associated with vulnerable carotid plaques consisting primarily of intraplaque hemorrhage and/or intraluminal thrombus. 12,13 Intraplaque hemorrhage might cause formation of intraluminal thrombus likely due to chemical mediators, increased stenosis, or changes in eddy currents, though the associations among these remain unclear. Other research has shown that more cerebrovascular adverse events related to CEA occurred in patients with atheromatous plaques compared with patients with fibrous plaques.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…22 Altaf et al 17 found that carotid IPH, observed on MR imaging scans, is significantly associated with an increased risk of microembolization, detected on a transcranial Doppler imaging scan during the dissection phase of carotid endarterectomy. They suggested that the presence of IPH is a strong indicator of a carotid plaque that is likely to cause embolization during endarterectomy, and therefore the patient has a higher perioperative risk.…”
mentioning
confidence: 99%